REFLEKSI CINTA DAN BENCI DALAM KARAKTER NIKOLE PADA NOVEL THE PROPOSAL KARYA JASMINE GALLORY - Aziz Satrio; Eka Yuniar Ernawati (Universitas Tribhuwana Tunggadewi, 2020)
Love and hate are very common happen in human life when they have relationship with others. In the literary work of novel, there are the writers who use the theme of their works about love and hate through the characters which they create. This research use Psichology Approachof Love and Hate.The researchers use the theory of triangular of love based on Sternberg’s journal and hate theory based on Krech and Dana Harron. Furthermore, this study focuses on Friends With Benefits relationship turns out to be true loveThis research aims to prove that love can come from anywhere, especially having a relationship with benefits and hatred is not always for revenge, because there is hatred we can find out what we like and dislike also not fall into the same thing as is done by Nikole and Carlos. Hatred brings them closer to each other and shares stories. This study uses the method of qualitative research, types of library research, interpretative analysis using the method of data collection in the form of literary texts from the novel The Proposal by Jasmine Guillory as a primary source and supported by some of the literatures to relate the theory, concept and the relevant definition as a secondary source. The result of this research is sometimes we have to get to know someone very deeply even though it hurts to see if love is true or not. I believe that hate doesn't always mean bad. Hate teaches us really khow to love someone right and love also generates hatred based on the character Nik is always in touch with his ex and indirectly compares his ex to Carlos because Nikole doesn't want to fall a second time in the same hole.